Phenomenological Anthropology and Ontological Turn: Crossed lives or Parallel paths? - García-Labrador, Julián (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This article shows the parallels and divergences of the ontological turn and phenomenological anthropology. Both currents, in fidelity to ethnographic data, share the rejection of the regime of representation and both currents bring into question the epistemic commitments of the researcher. However, the ontological turn presents a conceptual orientation, which often leads to typology, while phenomenological anthropology deals with the perceptive relations of the life world from a hermeneutic openness.